The Lead Lag Relationship between Spot and Futures Markets in the Energy Sector: Empirical Evidence from Indian Markets - Raju, Guntur Anjana; Shirodkar, Sanjeeta (International Journal of Energy Economics and Policy, 2020)
The study aims at finding the intraday Lead-Lag relationship between Spot and Futures Market for Energy Sectors Stocks on which Single Stock Futures (SSFs) is available, by applying 1-Minute Price Returns for the period ranging from 1st April 2017 to 31st March 2019. The study explores Price-Discovery between Stock Futures and their Underlying Stocks by applying Vector Error Correction Model, Hasbrouck (1995) Information Shares, and Common Factor Component Weights of Gonzalo and Granger (1995). The findings indicate that trades in the Futures Market contribute more to Price-Discovery than Spot Market. Keywords: Energy Sector, Single Stock Futures; Price-Discovery; Information share; VECM; Cointegration JEL Classifications: G11, G14 DOI: https://doi.org/10.32479/ijeep.9783